From Financial Crisis to Social Change Towards Alternative Horizons (Springer International Publishing, 2018)
Late neoliberalism marked a critical juncture that has upset socio-economic and political institutions. While certainly challenging democracy and increasing inequality, it also triggered progressive social movements with highly innovative characters. This volume helps us to understand their potential for building emancipatory alternatives to capitalism, by mobilizing the knowledge and experiences of a generation that the authors present as unemployed and discontented but also socially aware and politically active. -Donatella Della Porta, Professor of Political Science and Dean of the Institute for Humanities and the Social Sciences at Scuola Normale Superiore The repercussions of the financial crisis continue to shake the world's developed societies because they strike at basic contradictions in an era of great transformations. Not only economic but also political and, crucially, academic institutions remain in upheaval. This book delves into the full range and complexities of challenges and changes underway. -Craig Calhoun is Global Distinguished Professor of Sociology at New York University and Centennial Professor at the London School of Economics and Political Science This edited collection critically engages with a range of contemporary issues in the aftermath of the North Atlantic financial crisis that began in 2007. From challenging the erosion of academic authority to the myth that parliamentary democracy is not worth engaging with, it addresses three interrelated questions facing young people today: how to reclaim our universities, how to revitalise our democracy and how to recast politics in the 21st century. This book emphasises the crucial importance of generational experience as a wellspring for progressive social change. For it is the young generations who have come of age in a world marred by crises that are at the forefront of challenging the status quo. With insight into new social movements and protests in the UK, Canada, Greece and Ukraine, this stimulating collection of works will be invaluable for those teaching, studying and campaigning for alternatives. It will also be of relevance to scholars in social movement studies, the sociology and anthropology of economic life, the sociology of education, social and political theory, and political sociology.